Study of the Interaction of Phaseolus lunatus Hydrolysed Proteins and Delonix regia Carboxymethylated Gum Using Capillary Electrophoresis - Corzo Rios, Luis Jorge (2018)
Proteins and gums are commonly employed in the manufacture of processed foods. The knowledge of the degree of interaction between these two types of biopolymers is important for the development of new products and processes. In this work, the interaction of protein hydrolysate (PH) of Phaseolus lunatus with carboxymethylated flamboyant gum (CFG) was evaluated. Capillary electrophoresis technique was performed using a P/ACE MDQ equipment with diode array detector at 220 nm, using a 50 μm I.D. bare fused-silica capillary, with a 20 cm effective length, operating at 5 kV for injection and separation in reverse polarity at 15 kV and 25 °C. PH presented 7 main protein components of 8.3, 11.2, 12.9, 17.0, 19.1, 28.7 and 56.4 kDa. A standard curve with different concentrations of hydrolysed protein (3.8 to 8.6 g/L) was prepared by linking the relative peak height for each component present in the protein hydrolysate to its concentration. To determine the existence of PH-CFG interaction, protein-gum mixtures using different concentrations of PH and keeping constant the concentration of CFG at 2 or 2.8 g/ L were evaluated. Interaction PH-CFG was observed at 1.8-2.9 protein / gum ratios. Protein components of PH presented a tendency to join to CFG in a greater extent at lower molecular weight. Protein components higher than 20 kDa remain free in PH-CFG systems.